Separate aspects of the formation and state registration of environmental technological restrictions in land use - Dorosh, Y.; Kupriyanchyk, I. (Land Management, Cadastre and Land Monitoring, 2017)
The state of land use, the main problems underlying the provision of legal regulation of agricultural land in terms of establishment and registration restrictions in the use of agricultural land. An improved procedure for the formation and registration of state environmental and technological limitations in the use of land. Keywords: land protection, environmental and technological limitations, the type of restrictions, type constraints, land regulations.